Occipital Nerve Stimulation for the Treatment of Patients With Medically Refractory Occipital Neuralgia: Congress of Neurological Surgeons Systematic Review and Evidence-Based Guideline. Issue 3 (29th May 2015) - Sweet, Jennifer A.; Mitchell, Laura S.; Narouze, Samer; Sharan, Ashwini D.; Falowski, Steven M.; Schwalb, Jason M.; Machado, Andre; Rosenow, Joshua M.; Petersen, Erika A.; Hayek, Salim M.; Arle, Jeffrey E.; Pilitsis, Julie G.
Abstract: BACKGROUND: Occipital neuralgia (ON) is a disorder characterized by sharp, electrical, paroxysmal pain, originating from the occiput and extending along the posterior scalp, in the distribution of the greater, lesser, and/or third occipital nerve. Occipital nerve stimulation (ONS) constitutes a promising therapy for medically refractory ON because it is reversible with minimal side effects and has shown continued efficacy with long-term follow-up. OBJECTIVE: To conduct a systematic literature review and provide treatment recommendations for the use of ONS for the treatment of patients with medically refractory ON. METHODS: A systematic literature search was conducted using the PubMed database and the Cochrane Library to locate articles published between 1966 and April 2014 using MeSH headings and keywords relevant to ONS as a means to treat ON. A second literature search was conducted using the PubMed database and the Cochrane Library to locate articles published between 1966 and June 2014 using MeSH headings and keywords relevant to interventions that predict response to ONS in ON. The strength of evidence of each article that underwent full text review and the resulting strength of recommendation were graded according to the guidelines development methodology of the American Association of Neurological Surgeons/Congress of Neurological Surgeons Joint Guidelines Committee. RESULTS: Nine studies met the criteria for inclusion in this guideline. All articles provided Class III Level evidence. CONCLUSION: Based on the data derived from this systematic literature review, the following Level III recommendation can be made: the use of ONS is a treatment option for patients with medically refractory ON.